(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The paper provides key tactics and procedures for its translation and explores characteristics of English military slang. Functional equivalent, cultural equivalent, meaning extension, compensating, and retelling are some of these.